A New Homolodromioid Crab (Brachyura: Dromiacea: Tanidromitidae) from the Bajocian of Central Poland and a Review of the Stratigraphical Distribution and Paleoenvironments of the Known Middle Jurassic Homolodromioids. Issue 5 (1st September 2016) - Krobicki, Michał; Zatoń, Michał
Abstract: A new homolodromioid (Brachyura, Tanidromitidae) crab from the Middle Jurassic (uppermost Bajocian) of central Poland is described and a new species, Tanidromites muelleri, is erected. The new species is not only one of the oldest representatives of true crabs, but also the most numerous in the world in terms of collected individuals (46 carapaces, including incomplete specimens) of the Middle Jurassic homolodromioid crabs. Tanidromites muelleri sp. nov. lived in a shallow-water, soft-bottom marine environment around developing oyster patch-reefs, being similar as later during the Late Jurassic when they lived in association with extensive sponge bioherms and coral reefs. The preservation of carapaces of the new species was influenced by a quick burial and rapid mineralization of calcitic concretions in which they are embedded. The stratigraphic distribution, to ammonite subzone level, of homolodromioid Middle Jurassic crabs is reviewed. Analysis of their paleoenvironmental preferences indicated that during the first step in the origin of true crabs they were connected with shallow, marine, high-energy carbonate deposits dominated by oolitic (including ferrugineus-oolitic one) facies, coralliferous reefs, and grey/black clays with carbonate concretions which hosted these crabs.